Molecular Insights Into the Sensory Adaption of the Cave‐Dwelling Leech Sinospelaeobdella wulingensis to the Karst Cave Environment - Xi Wen; Haiyang Xiang; Mengqing Zhang; Aoran Yan; Dongqing Xiang; Jie Zou; Yue Zhang; Xinglong Huang; Zhixiao Liu (Ecology and Evolution)
ABSTRACT Karst caves are a unique environment significantly different from the external environment; adaptation of cave‐dwelling animals to the cave environment is often accompanied by shifts in the sensory systems. Aquatic and terrestrial leeches have been found in the karst caves. In this study, we conducted a transcriptome analysis on the cave‐dwelling leech Sinospelaeobdella wulingensis. A total of 29,286 unigenes were obtained by assembling the clean reads, and only 395 genes are differentially expressed in winter and summer samples. Two piezo‐type mechanosensitive ion channels (Piezos), eight transient receptor potential channels (TRPs), and six ionotropic glutamate receptors (iGluRs) were identified in the transcriptome. These channels/receptors are transmembrane proteins sharing conserved structural features in the respective protein families. SwPiezo1 shares high identity with Piezos in non‐caving leeches. SwiGluRs are conserved in protein sequence and share high identities with homologous proteins in other leeches. In contrast, SwTRPs belong to different subfamilies and share diverse identities with TRPs in other species. Gene expression analysis showed that two SwPiezos, five SwTRPs, and one SwiGluR are abundantly expressed in both winter and summer samples. These results suggest that SwPiezos, SwTRPs, and SwiGluRs are candidate sensory channels/receptors that may have roles in mechanosensory and chemosensory systems. High expression levels of Piezo and TRP genes imply a mechanosensory adaptation of S. wulingensis to the hanging living style in caves. Furthermore, enrichment of sensory genes in the oral sucker indicates the important role of this tissue in response to environmental stimuli. Similar gene expression profiles in winter and summer samples imply a stable physiological status of S. wulingensis in the cave environment.